2014
DOI: 10.1038/srep06679
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in Strong Spin Orbital Coupling Compound Sb2Se3

Abstract: Recently, A2B3 type strong spin orbital coupling compounds such as Bi2Te3, Bi2Se3 and Sb2Te3 were theoretically predicated to be topological insulators and demonstrated through experimental efforts. The counterpart compound Sb2Se3 on the other hand was found to be topological trivial, but further theoretical studies indicated that the pressure might induce Sb2Se3 into a topological nontrivial state. Here, we report on the discovery of superconductivity in Sb2Se3 single crystal induced via pressure. Our experim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 38 publications
4
52
0
Order By: Relevance
“…From this perspective, it is observed that the cation LEP is active in both polyhedral units of Sb2Se3, but only in one polyhedral unit of α-As 2 Te 3 ; i.e., the LEP activity of Sb in Sb 2 Se 3 is larger than that of As in α-As 2 Te 3 . This different LEP activity is a consequence that the cation LEP activity depends on the anion and increases for lighter anions as already reported elsewhere [31].…”
Section: Acknowledgmentsupporting
confidence: 81%
“…From this perspective, it is observed that the cation LEP is active in both polyhedral units of Sb2Se3, but only in one polyhedral unit of α-As 2 Te 3 ; i.e., the LEP activity of Sb in Sb 2 Se 3 is larger than that of As in α-As 2 Te 3 . This different LEP activity is a consequence that the cation LEP activity depends on the anion and increases for lighter anions as already reported elsewhere [31].…”
Section: Acknowledgmentsupporting
confidence: 81%
“…28 The largest natural surface was determined as (112) Pressure-induced superconductivity in Dirac semimetal Cd 3 As 2 L He et al hexagonal boron nitride. 9,13,14 The sample size is about 80 × 80 μm 2 in the (112) plane, with the thickness of ∼ 10 μm. The pressure was determined by ruby fluorescence method at room temperature before and after each cooling down.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11][12][13][14] High-pressure powder XRD measurements on Cd 3 As 2 were performed up to 17.80 GPa. In Figure 4, the XRD patterns below 2.60 GPa can be well indexed as the tetragonal phase in space group I4 1 /acd.…”
Section: Pressure-induced Superconductivitymentioning
confidence: 99%
See 2 more Smart Citations